Nanostructured Materials As Catalysts For The Production Of Gasoline From Used Palm Oil And Crude Palm Oil: Synthesis, Characterization And Activity Studies - Ahmad Shah, Noor Aisyah (2007)
Objektif penyelidikan ini adalah untuk menghasilkan mangkin peretakan yang efisien serta mempunyai kestabilan hidroterma yang baik